2016
DOI: 10.1080/15376516.2016.1197992
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acetylcholine, seizure activity and neuropathology following high-dose nerve agent exposure and delayed neuroprotective treatment drugs in freely moving rats

Abstract: Organophosphorus nerve agents such as soman (GD) inhibit acetylcholinesterase, producing an excess of acetylcholine (ACh), which results in respiratory distress, convulsions and status epilepticus that leads to neuropathology. Several drugs (topiramate, clobazam, pregnanolone, allopregnanolone, UBP 302, cyclopentyladenosine [CPA], ketamine, midazolam and scopolamine) have been identified as potential neuroprotectants that may terminate seizures and reduce brain damage. To systematically evaluate their efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 64 publications
3
8
1
Order By: Relevance
“…These data are consistent with those of other reports that have shown little or no effect of MDZ on neuronal death in delayed treatment (≥40 minutes) of NA‐induced SE . In contrast, treatment with MDZ at 10 to 20 minutes appears to be effective at reducing neuronal death . Our analysis of the change in power in the gamma band for up to 20 hours from the time of treatment suggests that the observed neuronal damage may be affected by the reemergence of epileptiform activity hours after treatment, which is similar to what has been previously shown by Wu et al …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data are consistent with those of other reports that have shown little or no effect of MDZ on neuronal death in delayed treatment (≥40 minutes) of NA‐induced SE . In contrast, treatment with MDZ at 10 to 20 minutes appears to be effective at reducing neuronal death . Our analysis of the change in power in the gamma band for up to 20 hours from the time of treatment suggests that the observed neuronal damage may be affected by the reemergence of epileptiform activity hours after treatment, which is similar to what has been previously shown by Wu et al …”
Section: Discussionsupporting
confidence: 92%
“…13,39,40 In contrast, treatment with MDZ at 10 to 20 minutes appears to be effective at reducing neuronal death. 40,46 Our analysis of the change in power in the gamma band for up to 20 hours from the time of treatment suggests that the observed neuronal damage may be affected by the reemergence of epileptiform activity hours after treatment, which is similar to what has been previously shown by Wu et al 40 The primary goal of the CNS Program is to provide a screening assay available to any participant who is interested in generating data toward application for grant funding from the CounterACT program. As such, the scope of the work here is limited to the development of a medium-throughput assay that somewhat models a real-life exposure scenario, and not open to traditional academic scientific endeavor.…”
Section: Neuroprotection By Mdz When Administered With Different Desupporting
confidence: 73%
“…Similarly, Beta Diversity were calculated using QIIME and visualized using Principal Coordinate Analysis (PCoA) to visualize distances between samples on an x-y-z plot. The ranked abundance profile was created using BiodiversityR R Bioconductor package (2 7-2…”
Section: Methods and Meterialsmentioning
confidence: 99%
“…Soman, pinacolyl methylphosphonofluoridate or GD (German agent D), is one of the G class nerve agents (volatile agents associated with inhalation toxicity) that inhibits AChE much more rapidly but less specifically than V class nerve agents (viscous agents associated with transdermal toxicity) (2, 6, 8). Whole body autoradiography studies in mice revealed that intravenously administered tritiated-soman ( 3 H-soman) spreads within the entire body in less than 5 min (9).…”
Section: Introductionmentioning
confidence: 99%
“…Acon‐Chen et al. () also studied the acute effects of soman and tested several drugs for their post‐exposure neuroprotectant properties versus seizures and neuropathology in rats. Striatal microdialysis was employed to monitor the changes in extracellular acetylcholine induced by soman: The neurotransmitter peaked 30 min post‐exposure at 8‐fold levels over baseline.…”
Section: Microdialysis In Neurotoxicology: Environmental Agentsmentioning
confidence: 99%